The Moderating Role of Vertical Collectivism in South-Korean Adolescents’ Perceptions of and Responses to Autonomy-Supportive and Controlling Parenting - Soenens, Bart; Park, Seong-Yeon; Mabbe, Elien; Vansteenkiste, Maarten; Chen, Beiwen; Van Petegem, Stijn; Brenning, Katrijn (Frontiers in Psychology, 2018)
Research increasingly demonstrates that associations between autonomy-relevant parenting and adolescent adjustment generalize across cultures. Yet, there is still an ongoing debate about the role of culture in these effects of autonomy-relevant parenting. The current study aimed to contribute to a more nuanced perspective on this debate by addressing cultural variability in micro-processes involved in autonomy-relevant parenting and, more specifically, in adolescents’ appraisals of and responses to parental behavior. In this vignette-based experimental study, involving 137 South-Korean adolescents (54% female, mean age = 16 years), we examined whether individual differences in vertical collectivism affect the association between descriptions of potentially autonomy-supportive and controlling parenting practices and (a) appraisals of these practices (in terms of perceived autonomy support and control and experiences of autonomy need satisfaction and frustration), and (b) anticipated responses to these practices (i.e., negotiation, submissive compliance, and oppositional defiance). Participants in the autonomy-supportive condition reported more perceived autonomy support and autonomy satisfaction and lower perceived control and autonomy need frustration than participants in the controlling condition. Collectivism moderated between-vignette effects on perceived control and autonomy need frustration such that the differences between the autonomy-supportive and controlling vignettes were less pronounced (yet still significant) among adolescents scoring higher on collectivism. Collectivism did not moderate effects of the vignettes on the responses to parenting, but yielded a main effect, with collectivism relating to more submissive compliance and less oppositional defiance. Overall, the results suggest that both universal and culture-specific processes are involved in autonomy-relevant socialization.